Opportunistic prophylactic salpingectomy for prevention of ovarian cancer: What do national societies advise?. (June 2018) - Ntoumanoglou-Schuiki, Angelika; Tomasch, Gordana; Laky, Rene; Taumberger, Nadja; Bjelic-Radisic, Vesna; Tamussino, Karl
Abstract: Objective: To determine how many FIGO (International Federation of Obstetrics and Gynecology) member societies have statements regarding opportunistic (incidental, prophylactic, risk-reducing) salpingectomy at the time of benign gynecologic surgery and to categorize statements as positive, negative or ambivalent. Study design: The websites of the 130 FIGO member societies were searched for statements on opportunistic salpingectomy. We looked for separate statements and statements embedded in other documents such as clinical guidelines as well as statements by national societies of gynecologic oncology. If nothing was found on the websites we contacted societies by Email or fax. Results: As of early 2018, 13 FIGO member societies representing 14 countries have statements regarding opportunistic salpingectomy. Nine were separate, stand-alone statements, four were embedded in other documents. Nine of the 13 statements (from Canada, Finland, U.S.A., Great Britain, Australia and New Zealand, Denmark, Austria, Turkey, and Japan) support consideration of opportunistic salpingectomy in appropriate women and four (from Germany, Sweden, Norway, and France) are ambivalent; there are no statements recommending against opportunistic salpingectomy. Conclusion: In 2018 only a small minority of FIGO members have statements on opportunistic prophylactic salpingectomy. These statements are ambivalent or supportive, none is negative.